The level of nervous disorder for Basrah University students - Majeed Issa, Heba (Social Empowerment Journal, 2020)
The study aimed to identify the level of nervous disorder for university students. According to the variables of sex (male - female) and specialization (scientific - human). The sample of the research reached (400) male and female students from the University of Basra distributed on (8) colleges, which were chosen by the stratified random method. And the researcher verified the psychometric properties of the scale by findingtheapparent validity and the validity of the construction. As for the reliability, it was verified by two methods: re-testing and the Alpha-Cronbach coefficient. The results were verified and their data processed statistically. The researcher used the appropriate statistical means, T-test for two independent samples, Pearson correlation coefficient, T-test for one sample, Alpha-Cronbach equation, and also used the Statistical Package for Social Sciences (SPSS). The results showed that university students have an average level in nervous disorder , as well as the presence of statistically significant differences in nervous disorder fot Basrah University students according to the gender variable and in favor of females and also the presence of statistically significant differences in the nervous disorder for Basrah University students according to specialization and in the interests of human specialization. Through the results of the study, the researcher came up with a set of recommendations and proposals.